Wound Healing Activity of Herbal Ointment Containing the Extracts of Hibiscus rosa-sinensis Flowers and Curcuma longa Rhizomes - Mustaffa, Fazlina; Parasuraman, Subramani; Sahgal, Geethaa (Free Radicals and Antioxidants)
Objectives: To evaluate wound healing activity of herbal ointment containing the extracts of Hibiscus rosa-sinensis flowers and Curcuma longa rhizomes. Methodology: H. rosa-sinensis flowers and C. longa rhizomes were extracted using 95% ethanol. H. rosa-sinensis and Hibiscus rosa-sinensis ointment were prepared using paraffin wax, lanolin and petroleum jelly. Ointment formulation was applied once daily on the excision wound made on Sprague Dawley rats for 20 days. Results: On day 20, the treatment group showed a significant increase in wound contraction which was 93.52 ± 1.38% when compared to control (87.62 ± 1.48%). Conclusion: Herbal ointment exhibited significant wound healing activity in rat excision wound model.
Keywords: Hibiscus rosa-sinensis; Curcuma longa; Wound healing